(untitled) (International Journal of Applied Research in Management and Economics, 2022)
This paper aims to identify the trends of territorial offer construction around the world in accordance with them opting for a territorial marketing strategy (TM). We proceed to the identification and then analysis of TM trends around the world. For this, we have opted for the methods of secondary data analysis (qualitative methodology), and this is through the exploration of the experiences of the chosen cases. We have been able to identify the practices that represent the best practices to develop in territorial offer build, and the mistakes to avoid. This benchmark has allowed sharing methods, techniques, and proven experiences in the TM field. The goal was to understand and not to model the strategies, we sought to generate an understanding of the Key Success Factors that make the success of the territorial.